2015
DOI: 10.1364/ol.40.005255
|View full text |Cite
|
Sign up to set email alerts
|

Ytterbium-doped fiber ultrashort pulse generator based on self-phase modulation and alternating spectral filtering

Abstract: We numerically and experimentally demonstrate a Yb-doped fiber ultrashort pulse generator based on self-phase modulation and alternating spectral filtering, operating at a wavelength of 1060 nm and providing a stable ultrashort pulse train. Pulses with energy up to 2.8 nJ were generated experimentally and were limited only by available pump power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…In previously reported studies, Mamyshev technology was used for mostly high-power pulse generation [40]- [42]. Exploiting the self-phase-modulation (SPM)-induced spectral broadening and offset spectral filtering of Mamyshev regeneration, unprecedented nonlinear phase shifts can be obtained, and higher peak powers can be achieved [43].…”
Section: A Working Principle Of the Multi-wavelength Synchronous Lasermentioning
confidence: 99%
“…In previously reported studies, Mamyshev technology was used for mostly high-power pulse generation [40]- [42]. Exploiting the self-phase-modulation (SPM)-induced spectral broadening and offset spectral filtering of Mamyshev regeneration, unprecedented nonlinear phase shifts can be obtained, and higher peak powers can be achieved [43].…”
Section: A Working Principle Of the Multi-wavelength Synchronous Lasermentioning
confidence: 99%
“…The main limitation of fiber Mamyshev oscillator is that the operation in the anomalous group-delay dispersion (GDD) regime is prohibitive due to the high energy pulse breakup problem. Fiber Mamyshev oscillators to date work either at 1 µm where the normal GDD fiber is readily available [8,[11][12][13] or at 1.5 µm where specialty fibers can be utilized to shift the GDD [14]. Operation at longer wavelengths with Tm-doped silica fiber and Er-doped ZBLAN fiber, characteristic of large anomalous GDD and Kerr nonlinearity, thus poses a nontrivial challenge [9].…”
Section: Introductionmentioning
confidence: 99%
“…Regelskis et al first demonstrated a Mamyshev oscillator aimed at high-energy femtosecond pulses [18]. This environmentally-stable oscillator produced modestenergy (<3 nJ) pulses about 2 ps in duration.…”
Section: Introductionmentioning
confidence: 99%